Audit Committee Effectiveness and Earnings Management Among Publicly Listed Firms in Kenya - Collins Kapkiyai; Josephat Cheboi; Joyce Komen (SEISENSE Journal of Management, 2020)
Objective: The paper sought to investigate the role of an effective audit committee in controlling earnings management practices.